Cover Picture: Astron. Nachr. 03/2023. Issue 3 (23rd April 2023) - Griggio, M.; Nardiello, D.; Bedin, L. R.
Abstract : Vector plots of the Geometric distortion (GD) solution for the James Webb Telescope NIRCam long wavelength channel detectors #5 of both module A (left) and module B (right), showing the size of the residual vectors, magnified by a factor of 20. The color map represents the pixels' area variation across the detectors due to the GD correction. Details are presented in the article by M. Griggio et al. (this issue of AN, e230006 ) where the authors describe their correction procedure and its validation. Along with their geometric‐distortion solution, they make available their Python software to convert the raw‐pixels coordinates of each detector into distortion‐free positions, and to put all ten detectors of NIRCam into a common reference system.